Legg-Calvé-Perthes disease. Issue 5 (September 2015) - Fornari, Eric D.; Karkenny, Alexa; Schulz, Jacob
<x xml:space="preserve">Abstract</x> Over a century has passed since the first reported cases of Legg-Calvé-Perthes disease (LCPD) appeared in the literature. While it is generally accepted that LCPD results from disruption of blood supply to the capital epiphysis, the underlying etiology has remained elusive. The overriding goal in treating LCPD is to maintain a concentrically reduced hip with a spherical femoral head to prevent the development of degenerative changes in the young adult hip. Treatment options are based on the age of presentation, deformity present during active disease, or residual deformity at skeletal maturity. The majority of research has focused on diagnosis and management of LCPD during the early active phases. As our understanding of femoral acetabular impingement has evolved so too has our ability to safely treat the residual deformity characteristic of LCPD. This review focuses on the newest available literature concerning the diagnosis and treatment of LCPD in children and young adults.